PENGARUH MASA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH DASAR DI DESA SAMUDRA DAN SAMUDRA KULON - Sugito Sugito; Y Suyitno; Kuntoro Kuntoro (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This research aims to identify: 1) the influence of working time on teacherperformance, 2) the influence of motivation on teacher performance, and 3) theinfluence of working time and motivation on performance of elementary school teachersin the villages of Samudra and Samudra Kulon. This research is ex-post facto lookingfor causal relationships, to reveal facts based on measurements of symptoms that haveoccurred in each respondent. Determination of the sample in this study is a saturatedsample, where all members of the population become the object of research. Totalpopulation is 50 people. The analysis carried out was a simple and multiple correlationanalysis and regression analysis. Respondents in this research have a working time of 2to 32 years. The results of this research are (1) there is a negative influence on theworking time variable on teacher performance; (2) there is a positive influence on themotivation variable on teacher performance; and (3) there is a positive influence onworking time and motivation on performance. The effective contribution of working timeand motivation to performance are 8.9% and 18%, respectively. The relativecontribution of working time and motivation to performance are 33% and 67%,respectively.